Effects of noise and measurement error on load reconstruction of dynamic loads in the frequency domain - Heyns, P.S. (Philippus Stephanus) (University of Pretoria, 2024)
Dissertation (MEng (Mechanical Engineering))--University of Pretoria, 2024.